Principal-Led Programs in Fostering Religious School Culture: A Case Study of Public Secondary Schools - Ilyas Maulana; Istanto Istanto (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
Public schools often emphasize academic achievement while giving limited attention to students’ religious and moral development. However, parents’ expectations toward education have shifted, demanding schools that are not only academically excellent but also capable of fostering strong religious character. This study aims to explore how principal-led programs contribute to the realization of a religious school in a public secondary school context. The research was conducted at SMP Negeri 1 Jogorogo, Ngawi Regency, a public school recognized for its strong religious culture and academic performance. This study employed a qualitative field research design using a phenomenological approach to understand participants’ lived experiences related to religious program implementation. Data were collected through observation, in-depth interviews, and document analysis involving the principal and selected teachers. Data analysis was conducted continuously using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of sources and techniques. The findings indicate that the principal plays a central role in fostering a religious school culture through structured, sustainable, and value-based programs. Six core programs were identified: Qur’anic memorization (tahfidz), orphan sponsorship, dawn charity (sedekah subuh), professional zakat, routine religious study sessions, and the “three day one juz” Qur’anic recitation program. These programs are strengthened by effective leadership strategies, including ideological integration with teachers, openness to feedback, and continuous motivation. The study concludes that strong principal leadership combined with well-designed religious programs significantly contributes to the development of a religious culture in public schools without compromising academic excellence.